« Les Mains du tueur Weidmann » - Nicolas Bianchi (Criminocorpus)
This paper questions the media strategy of the magazine Détective when the Weidmann affair came out, which involved a German serial murderer, whose motives were quite unclear, in 1937. The weekly review wanted to distinguish itself from the daily press by using many stylistic, narrative and iconographic tools in such a way as to make its name inseparable from this major criminal affaire. It also took part in creating the media figure of a monster by rewriting his personal intimate story, tracing his roots back to a devilish lineage and, further, by exhibiting and judging his body, which appeared simultaneously scary, fascinating and harmless because of the physical coercions he had suffered. Through this strategy, our paper also tries to question the controversial definition of « fait divers » that a structural approach developed, thus explaining some of the narratives difficulties that Détective encountered.